Stock Prices, News, and Economic Fluctuations: Comment - Kurmann, André; Mertens, Elmar (American Economic Review, 2014)
Beaudry and Portier (2006) propose an identification scheme to study the effects of news shocks about future productivity in vector error correction models (VECMs). This comment shows that, when applied to their VECMs with more than two variables, the identification scheme does not have a unique solution. The problem arises from a particular interplay of cointegration assumptions and long-run restrictions. (JEL E32, E44, G12, G14)